Μελέτη, εξαγωγή και αξιοποίηση σχεσιακών μοντέλων μεταξύ εικονικών οντοτήτων στο κοινωνικό διαδίκτυο των πραγμάτων - Σπαθαριώτη, Σοφία-Ελένη (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής & Συστημάτων Πληροφορικής, 2015)
The Internet of Things is a network of physical objects supplied with unique identifiers and appropriate mechanisms in order to communicate with other objects, without the need of human interaction. This area has grown popular over the years due to a variety of applications, ranging from Home Automation to Healthcare. A recent approach to the IoT is the social Internet of Things (sIoT), where objects communicate based on social characteristics. The concept that motivated this thesis lies in creating an efficient knowledge flow in the Internet of Things, through the formation of social relationships. Things acquire information, that is shaped in the form of knowledge based on other objects' experiences. The ultimate goal of this thesis is to facilitate autonomy in the social Internet of Things by proposing appropriate object relationships to serve the knowledge flow in the network. After an introduction to the necessary background is provided to the reader, the main subject of this thesis is presented. The first part deals with establishing the main ontologies of the proposed structure of the sIoT; Virtual Entities, Applications and Users. Each ontology is defined by a set of given properties, which will be used in establishing the proposed Relational Models. Afterwards, the ten proposed Relational Models are analyzed. Each object relationship is explored in detail, by providing information in the form of characteristics, requirements for formation and elements of Relational Models Theory. Motivation and challenges behind each object relationship are also detailed, along with analytic scenarios. Finally, simulation on a sample network is conducted, through the use of the Gephi platform. Each object relationship is also individually simulated and observations based on simulation are discussed.